EKSISTENSI MASYARAKAT HUKUM ADAT SAKAI TERHADAP TANAH ULAYAT YANG TERDAPAT PADA KAWASAN HUTAN TANAM INDUSTRI - Annisa Faradina Annisa Faradina; Andi Suriyaman M. Pide; Sri Susyanti Nur (JURNAL ILMIAH LIVING LAW, 2023)
The existence of the indigenous people of the Sakai Tribe has met the requirements to be recognized as stipulated in Article 67 paragraph (1) of Law no. 41 of 1999 concerning Forestry, namely that the community is still in the form of an association (rechsgemeenschap), there are institutions in the form of customary rulers, there is a clear customary law area, there are legal institutions and instruments, especially customary courts, which are still adhered to and still collect forest products. in the surrounding forest area to meet the needs of daily life. Confirmation of the existence and elimination of customary law communities based on Article 67 paragraph (2) is stipulated by a Regional Regulation. However, until now there is no local regulation that regulates the existence of the indigenous peoples of the Sakai Tribe, thus creating legal uncertainty. Settlement of land boundary disputes between customary law communities and PT. Arara Abadi was resolved through litigation, in this case through the Bengkalis District Court as stated in the decision number 89/Pid.B/LH/2020/PN.Bls. In addition, dispute resolution outside the non-litigation legal route (mediation) has also been carried out in resolving border disputes between the Sakai Tribe customary law community and PT. Eternal Arra. Dispute resolution is carried out by deliberation by involving the inner group with PT. Arara is Eternal and there is usually peace Keywords: Existence, Sakai Tribe, Industrial Planting Forest.